2022
DOI: 10.3390/ijms232113099
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Cancer Expression in Oral Lichen Planus: A Scoping Review of Systematic Reviews and Meta-Analyses

Abstract: Oral lichen planus (OLP) is a common chronic inflammatory disease of unknown etiology and likely autoimmune nature that is currently considered an oral potentially malignant disorder, implying that patients suffering from this process are at risk of developing oral cancer in their lifetime. The molecular alterations that develop in OLP and that make the affected oral epithelium predisposed to malignancy are unknown, although, as in other autoimmune diseases (ulcerative colitis, primary biliary cirrhosis, etc.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 251 publications
0
4
0
Order By: Relevance
“…Understanding the oncogenic mechanisms linked to autoimmunity is complex, partly as a consequence of the inherent heterogeneity in the development of the immune response. To date, more than 30 primarylevel studies have been published analyzing the influence of the immune response on the malignant transformation of OLP, which frequently report the role of hyperproliferative stimuli and the hyperactivity of oncogenes with tumor suppressor gene responses [144,145]. Nevertheless, there are no systematic reviews or meta-analyses based on evidence regarding this particular subject.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the oncogenic mechanisms linked to autoimmunity is complex, partly as a consequence of the inherent heterogeneity in the development of the immune response. To date, more than 30 primarylevel studies have been published analyzing the influence of the immune response on the malignant transformation of OLP, which frequently report the role of hyperproliferative stimuli and the hyperactivity of oncogenes with tumor suppressor gene responses [144,145]. Nevertheless, there are no systematic reviews or meta-analyses based on evidence regarding this particular subject.…”
Section: Discussionmentioning
confidence: 99%
“…Under the action of exogenous antigens and autoantigens, abnormal apoptosis of oral mucosal keratinocytes mediated by cellular immunity was considered to be closely associated with the progression of OLP lesions. [8][9][10] As the development of next-generation sequencing technology, microarrays combined with bioinformatics analysis have been used widely to identify potential biomarkers for various complex diseases, which has provided new strategies for biomedical research. [11][12][13] Meanwhile, using bioinformatics research, Rivera C et al discovered that CXCL12 and its receptor gene CXCR4 were expected to monitor OLP occurrence and could be new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of exogenous antigens and autoantigens, abnormal apoptosis of oral mucosal keratinocytes mediated by cellular immunity was considered to be closely associated with the progression of OLP lesions. [8–10]…”
Section: Introductionmentioning
confidence: 99%
“…The probability of developing cancer in the oral cavity is around 1% in the presence of lichen planus. 9 Recently, many studies have shown the presence of immunological markers in the course of lichen planus, offering prospects for improved diagnostics and modern treatment. This provide hope for non-invasive diagnostic.…”
Section: Introductionmentioning
confidence: 99%